Can Levodopa Challenge Testing Predict the Effect of Deep Brain Stimulation? One-Year Outcomes in a Chinese Cohort - Lin, Wei; Shi, Dongliang; Wang, Dan; Yang, Likun; Wang, Yuhai; Jin, Lingjing (Frontiers in Aging Neuroscience, 2021)
Objective: Our study examined whether levodopa challenge test (LCT) results could predict quality of life (QoL) outcomes after surgery to implant subthalamic nucleus deep brain stimulation (STN-DBS) electrodes to treat advanced Parkinson’s disease (PD). Methods: Forty patients with STN-DBS underwent a follow-up 1 year after implantation surgery to analyze the correlation between preoperative levodopa impact test results and postoperative Unified Parkinson’s Disease Rating Scale (UPDRS) III motor score, postoperative PD Questionnaire-39 (PDQ-39) score, and PDQ-39 improvement. Results: Improvements in QoL were associated with several preoperative characteristics including preoperative UPDRS-III tremor, UPDRS-III tremor (off-60) (p = 0.049), UPDRS-III tremor (off-120) (p = 0.012), Mini-Mental State Examination (p = 0.012), and PDQ-39 (p = 0.012) before surgery. Multiple linear regression model using preoperative MMSE [odds ratio (OR) = 0.342, 95% confidence interval (CI) = 0.051–2.297], preoperative UPDRS-III tremor (OR = 2.099, 95% CI = 0.585–7.535), UPDRS-III tremor (off-60) [OR = 1.316, 95% CI = 0.804–2.154, UPDRS-III tremor (off-120) OR = 0.913, 95% CI = 0.691–1.207], correctly classified 88.5% of patients. Conclusion: Levodopa challenge test results cannot predict the effect of DBS. However, the test can be incorporated into a regression prediction model to the quality of life of PD patients after DBS with other preoperative factors.